Post Amendment of Judicial Review in Indonesia: Has Judicial Power Distributed Fairly? (Journal of Indonesian Legal Studies, 2022)
Distribution of power in Indonesian constitutional system not only occur amongst state organs but also within Indonesian judicial system. The Supreme Court and Constitutional Court share their power to review several regulations. The 1945 Constitution delivers power to review act against constitution for Constitutional Court and to review regulations below an act for the Supreme Court. However, this distribution of power is vulnerable to contradicting each other, with the possibility of having clash of judgment. There is no guarantee that the Supreme Court will fully obey the Constitutional Court judgment. So, the research question needs to be solved such as judicial Review pre-the Amendment of the 1945 Constitution process, and judicial Review Post the Amendment of the Constitution implement, that will be main points of research purposes. Furthermore, the main problem is the distribution power between Constitutional Court and Supreme Court, whether have distributed fairly or not. Another problem after amendment is about disagreement amongst judges. Before amendment, judges were forbidden to show their disagreement clearly in the verdict, but now allowed. This fact has led to public distrust. They have questioned the legitimacy of the verdict having disagreement, whether should be obeyed or be denied.